Early influences on blood pressure: a study of children aged 5-7 years. Issue 6699 (2nd September 1989) - Whincup, P. H.; Cook, D. G.; Shaper, A. G.
Abstract : OBJECTIVE--To examine factors that influence blood pressure in children. DESIGN--Cross sectional study of children aged 5.0-7.0 years who had blood pressure measurements and for whom parental questionnaires were completed. SETTING--School based survey. SUBJECTS--3591 Children aged 5.0-7.5 years selected by stratified random sampling of primary schools in nine British towns (response rate 72%); 3591 were examined and their parental questionnaires were completed. Data were complete for birth rank in 3559, maternal age in 3542, maternal history of hypertension in 3524, and paternal history in 2633. RESULTS--Birth weight was inversely related to mean systolic blood pressure but only when standardised for current weight (weight standardised regression coefficient -1.83 mm Hg/kg (95% confidence interval -1.31 to -2.35). Mean diastolic pressure was similarly related to birth weight. Maternal age, birth rank, and a parental history of hypertension were all related to blood pressure. After standardisation for current weight a 10 year increase in maternal age was associated with a 1.0 mm Hg (0.4 to 1.6) rise in systolic pressure; first born children had systolic blood pressure on average 2.53 mm Hg (0.81 to 4.25) higher than those whose birth rank was greater than or equal to 4; and a maternal history of hypertension was associated with a systolic pressure on average 0.96 mm Hg (0.41 to 1.51) higher than in those with no such history. The effects described were largely independent of one another and of age and social class. The relation for birth rank was, however, closely related to that for family size. CONCLUSIONS--Influences acting in early life may be important determinants of blood pressure in the first decade. The relation between birth weight and blood pressure may reflect the rate of weight gain in infancy. The reasons for the relation with birth rank and maternal age are unknown; if confirmed they imply that delayed motherhood and smaller family size may be associated with higher blood pressure in offspring.